La crisi familiare e le giurisdizioni religiose negli Stati Uniti: tensioni tra separatismo e pluralismo nel sistema delle ADR (Stato, Chiese e pluralismo confessionale, 2024)
Familiar crisis and religious jurisdictions the United States: tensions between separatism and pluralism in the ADR systemABSTRACT: In the United States, religious denominations play a central role in the out-of-court resolution of disputes. In fact, religious groups provide negotiation facilitation, mediation and arbitration services, according to models of increasing procedural complexity and binding nature. The contribution will illustrate case law guidelines about law enforcement of Jewish and Islamic judgements in familiar matters. I will focus on attempts of secular courts to mediate between opposing demands: the security of legal statuses, the maintenance of social stability and public order, the protection of rights of the individual, the deflation of civil litigation, the greater confidence of litigants towards the minister of religion acting as judge. In the conclusion, I will evaluate the impact of these trends on the intercultural paradigm that characterizes the American pluralist legal system.SOMMARIO: 1. Le ADR religiose negli Stati Uniti tra luci e ombre - 2. Pactum suprema lex esto? Il riconoscimento dei lodi arbitrali emessi dai tribunal rabbinici in sede di divorzio - 3. Il diritto familiare musulmano tra ostracismo e neutralità - 4. E pluribus unum? Il molteplice e il singolo di fronte allegiurisdizioni religiose nella società americana